The deformation characteristics of a 12% chromium steel - Brink, Andrew (Centre for Materials Engineering, 2024)
[page iii missing] Chromium is an essential alloying element in the stainless steel industry, where addition of a minimum of eleven percent of this material to iron can impart to the resulting alloy a degree of resistance to corrosive chemical attack •. It was against a bacKground of vast South African reserves of chromite ore and of an ever expanding market for corrosion resistant materials world-wide that Middleburg Steel & Aloys {PTY) Ltd. embarked on a programme to develop a high strength, 1 ow alloy, chrorni um steel which could be a cost effective replacement for coated mild steel. Due to the expense of chromium as an alloying element, however, it was planned that the cost benefit over ·1ow carbon steel would be achieved through the possible lowering of maintainance costs resultant from improved corrosion resistance. In addition to this, the consequence of an increased strength to weight ratio over mild steel could realize an economical materials saving through the use of reduced component cross sections.